Pelatihan penggunaan Artificial Intelligence di SMAN 1 Tanjung Bintang - Nirwana Hendrastuty; M. Ghufroni An’ars; Damayanti Damayanti; Samuel Hutagalung; Chris Mario; M. Tova (Journal of Engineering and Information Technology for Community Service, 2023)
Artificial intelligence is a part of computer science that studies how to make machines (computers) do jobs like and as well as humans, even better than what humans do. Artificial Intelligence is also often referred to as a science that studies how to make computers do things like humans do. Artificial intelligence is also an area of research, applications and instructions related to computer programming to do things, in the view of humans are intelligent. One of the artificial intelligence technologies is an expert system which is a computer program that can imitate the thought process and expert knowledge to solve a specific problem. The target of this activity is students of class XI and XII from SMAN 1 Tanjung Bintang. The implementation of community service for the assisted school scheme consists of three stages, namely, preparation, implementation and evaluation. The preparatory stage is carried out by carrying out a survey first to find out the problems experienced by partners and carry out an analysis to find solutions to these problems. From the results of the distribution of questionnaires in the training, it was found that there was an increased understanding of d the use of AI, especially in particular Chat GPT, with an average of 1.6, whereas previously students had an average pre-test of 4.0. and post-test of 5.6